2017
DOI: 10.1016/j.ebiom.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Targeted Next-Generation Sequencing Platform for Molecular Screening and Clinical Genotyping in Subjects with Hemoglobinopathies

Abstract: Hemoglobinopathies are among the most common autosomal-recessive disorders worldwide. A comprehensive next-generation sequencing (NGS) test would greatly facilitate screening and diagnosis of these disorders. An NGS panel targeting the coding regions of hemoglobin genes and four modifier genes was designed. We validated the assay by using 2522 subjects affected with hemoglobinopathies and applied it to carrier testing in a cohort of 10,111 couples who were also screened through traditional methods. In the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 34 publications
2
119
0
Order By: Relevance
“…The 5′ breakpoint of these two deletions was very similar to this 223 kb deletion, both with a similar 5′ breakpoint to this case (Figure A). Three mechanisms may contribute to this different HbF level: (a) the 3′ breakpoints of the above two deletions were different from the present case; (b) the expression of HbF is regulated by many genetic modifiers such as XmnI polymorphism, KLF1, BCL11A, HBS1L, and MYB . The NGS data of our cases showed that they were all negative for mutations in these factors, while this information was absent for the carriers of the above two deletions; and (c) the 5′ breakpoint of the 223 kb deletion was not completely consistent in the above two deletions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 5′ breakpoint of these two deletions was very similar to this 223 kb deletion, both with a similar 5′ breakpoint to this case (Figure A). Three mechanisms may contribute to this different HbF level: (a) the 3′ breakpoints of the above two deletions were different from the present case; (b) the expression of HbF is regulated by many genetic modifiers such as XmnI polymorphism, KLF1, BCL11A, HBS1L, and MYB . The NGS data of our cases showed that they were all negative for mutations in these factors, while this information was absent for the carriers of the above two deletions; and (c) the 5′ breakpoint of the 223 kb deletion was not completely consistent in the above two deletions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, individuals who are compound heterozygous for a large deletion and point mutation would be misdiagnosed as homozygous for the point mutation, such as the proband III 1 in this family. Similar examples were also reported by Shang 2017 . Therefore, molecular screening methods should be prioritized in areas with high incidence of thalassemia to increase the detection rate of genetic mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copy number variations (CNVs) of the α‐ and β‐globin gene clusters were analysed by multiplex ligation dependent probe amplification (MLPA) (Hu et al , ). Next generation sequencing (NGS) was also used to confirm the HBA rearrangement region and other mutations of modifier genes (Shang et al , ). To verify the duplication breakpoints, three pairs of primers were designed upstream and downstream of this rearrangement region, based on the NGS results, as follows (Fig C):…”
Section: Patient and Methodsmentioning
confidence: 99%